Waste Composting for Urban and Peri-Urban Agriculture: Closing the Rural-Urban Nutrient Cycle in Sub-Saharan Africa 2001
DOI: 10.1079/9780851995489.0001
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of waste-stream products for soil amelioration in peri-urban interface agricultural production systems.

Abstract: This review had an international rather than a country-specific focus although most of the examples cited were from developing countries. The review formed part of a strategy to develop and promote cost-effective techniques for recycling/processing organic waste-stream products (municipal waste, night soil and sewage sludge, poultry manures, and agroindustrial wastes from crop processing and livestock) for use as a fertilizer and contributed to the wider goal to increase productive potential by greater use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…• the cultivation of dumpsites (closed or operating) (Furedy and Ghosh, 1984;Drescher, 1994;Furedy, 2002); • the 'mining' of dumpsites for organic matter (see Rosenberg and Furedy, 1996: 72;Scheu and Bhattacharya, 1995;Nunan, 2000;Brook and Davila, 2000;Djabatey, 1996;Asomani-Boateng, 1999;Harris et al, 2001;Kiango and Amend, 2001); • the transportation of mixed solid waste to farms, where inorganics are largely removed before the waste is applied to soils (Lewcock, 1995;WASTE, 1998;IBSRAM, 2000;Nunan, 2001;Dulac, 2001); • on-farm co-composting of urban animal and farm wastes (which also applies to 'backyard farms') (Birley and Lock,1999:139;Nunan, 2001).…”
Section: Customary and Informal Practices In Recovery And Reuse Of Ormentioning
confidence: 99%
“…• the cultivation of dumpsites (closed or operating) (Furedy and Ghosh, 1984;Drescher, 1994;Furedy, 2002); • the 'mining' of dumpsites for organic matter (see Rosenberg and Furedy, 1996: 72;Scheu and Bhattacharya, 1995;Nunan, 2000;Brook and Davila, 2000;Djabatey, 1996;Asomani-Boateng, 1999;Harris et al, 2001;Kiango and Amend, 2001); • the transportation of mixed solid waste to farms, where inorganics are largely removed before the waste is applied to soils (Lewcock, 1995;WASTE, 1998;IBSRAM, 2000;Nunan, 2001;Dulac, 2001); • on-farm co-composting of urban animal and farm wastes (which also applies to 'backyard farms') (Birley and Lock,1999:139;Nunan, 2001).…”
Section: Customary and Informal Practices In Recovery And Reuse Of Ormentioning
confidence: 99%
“…Agriculture production contributes significantly to economic development in Nigeria. Among crops Irish potato (Solanum tuberosum L.) ranks fourth in the world in terms of economic importance (Harris et al, 2017). Developing countries account for 25% of the world potato production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some compost contains other growth-promoting substances such as B vitamins, natural hormones and organic acids. Harris et al [33] said that compost that has been made from a variety of materials is likely to provide the best spectrum of nutrients. Lopez-Real [34] in his study, showed that market waste co-composted with saw dust improves crop yield considerably while Cross and Strauss [35] showed that soil nutrients is greatly improved with the use of urban waste.…”
Section: Introductionmentioning
confidence: 99%